Respon Pemberian Pupuk Nitrogen dan Media Tanam Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Main Nursery - Siti Khairani; Tebe Holo Purba; Juhardi Sembiring (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Oil palm (Elaeis guineensis Jacq.) is a plantation commodity that has become highly favored in Indonesia. The massive expansion of oil palm plantations through large-scale land clearing has created new problems that impact the availability of suitable land for oil palm cultivation, making it limited and difficult to obtain. Consequently, the land currently used for cultivation and nursery is less suitable. Producing high-quality oil palm seedlings is closely linked to maintenance practices, the use of superior varieties, and the growing media used during the nursery phase. The growing media is a significant determining factor as it is the medium in which plant roots develop and absorb various essential nutrients for the plant's survival. In addition to the use of growing media, the application of nitrogen fertilizer aims to increase the availability of nutrients that can be absorbed by the plant for optimal growth. This research aims to determine the effects of growing media and nitrogen fertilizer application, as well as the interaction between these treatments, on the growth of oil palm seedlings in the main nursery. The study employs a factorial Randomized Block Design (RBD) with 2 treatment factors. The first factor is the planting media with 3 levels of treatment (M1: topsoil (3 parts) and rice husk charcoal (1 part), M2: topsoil (3 parts) and compost (1 part), M3: topsoil (3 parts), rice husk charcoal (0.5 part), and compost (0.5 part)). The second factor is the application of nitrogen fertilizer with 4 levels of treatment (N0: control, N1: 4 g/polybag, N2: 8 g/polybag, N3: 12 g/polybag). The results show that the growing media has a significant effect on increasing stem diameter. Nitrogen fertilizer significantly increases plant height and stem diameter. The interaction between growing media and nitrogen fertilizer significantly affects the increase in stem diameter of oil palm seedlings.